Analisis Penerapan PSAP No. 13 Tentang Badan Layanan Umum pada Universitas Islam Negeri Syarif Hidayatullah Jakarta (Jurnal Kendali Akuntansi, 2023)
Higher education is a government entity that has the status of a Public Service Agency. To realize the achievement of improving the quality of education, higher education requires good management. One way is through the implementation of regulations in PSAP No. 13. This study discusses the compatibility between the regulations in PSAP No. 13 with the reality that occurred at Syarif Hidayatullah State Islamic University Jakarta. The result is that Syarif Hidayatullah State Islamic University Jakarta has implemented most of the regulations contained in PSAP No. 13.